TGFBR2-dependent alterations of exosomal cargo and functions in DNA mismatch repair-deficient HCT116 colorectal cancer cells - Fricke, Fabia; Lee, Jennifer; Michalak, Malwina; Haußer-Siller, Ingrid; Suarez-Carmona, Meggy; Halama, Niels; Kopitz, Jürgen; Gebert, Johannes (Cell communication and signaling, 2017)
Colorectal cancers (CRCs) that lack DNA mismatch repair function exhibit the microsatellite unstable (MSI) phenotype and are characterized by the accumulation of frameshift mutations at short repetitive DNA sequences (microsatellites). These tumors recurrently show inactivating frameshift mutations in the tumor suppressor Transforming Growth Factor Beta Receptor Type 2 (TGFBR2) thereby abrogating downstream signaling. How altered TGFBR2 signaling affects exosome-mediated communication between MSI tumor cells and their environment has not been resolved. Here, we report on molecular alterations of exosomes shed by MSI cells and the biological response evoked in recipient cells.